Automation, Monitoring, and Standardization of Cell Product Manufacturing - Doulgkeroglou, Meletios-Nikolaos; Di Nubila, Alessia; Niessing, Bastian; König, Niels; Schmitt, Robert H.; Damen, Jackie; Szilvassy, Stephen J.; Chang, Wing; Csontos, Lynn; Louis, Sharon; Kugelmeier, Patrick; Ronfard, Vincent; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Although regenerative medicine products are at the forefront of scientific research, technological innovation and clinical translation, their reproducibility and large-scale production are compromised by automation, monitoring and standardisation issues. To overcome these limitations, new technologies at software (e.g. algorithms and artificial intelligence models, combined with imaging software and machine learning techniques) and hardware (e.g. automated liquid handling, automated cell expansion bioreactor systems, automated colony-forming unit counting and characterisation units and scalable cell culture plates) level are under intense investigation. Automation, monitoring and standardisation should be considered at the early stages of the developmental cycle of cell products to deliver more robust and effective therapies and treatment plans to the bedside, reducing healthcare expenditure and improving services and patient care.